1997
DOI: 10.1021/jo961696a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Esterase-Sensitive Cyclic Prodrug of a Hexapeptide Using an (Acyloxy)alkoxy Promoiety

Abstract: Synthetic methodology for preparing novel esterase-sensitive cyclic prodrugs of peptides with increased protease stability and cell membrane permeability compared to linear peptides is described. Cyclic prodrug 1 of the hexapeptide H-Trp-Ala-Gly-Gly-Asp-Ala-OH linked by the N-terminal amino group to the C-terminal carboxyl group via an (acyloxy)alkoxy promoiety was synthesized. A convergent synthetic approach involving Boc[[(alaninyloxy)methyl]carbonyl]-N-tryptophan (2) and H-Ala-Gly-Gly-Asp(OBzl)-OTce (3) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 41 publications
(48 reference statements)
1
46
0
Order By: Relevance
“…NMR spectra showed that the hydrolysis product can be identified with the desired linear peptide (see Supporting Information), as similarly proposed for cyclic prodrugs of opioid peptides. 14 For predicting the capacity of CP11 to cross the biological barriers, PAMPA assays were performed. To evaluate the GI permeation, the studies were implemented at pH 5.0, 6.5, and 7.4 with an 18 h incubation time; the pH of acceptor and donor compartments was always the same.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR spectra showed that the hydrolysis product can be identified with the desired linear peptide (see Supporting Information), as similarly proposed for cyclic prodrugs of opioid peptides. 14 For predicting the capacity of CP11 to cross the biological barriers, PAMPA assays were performed. To evaluate the GI permeation, the studies were implemented at pH 5.0, 6.5, and 7.4 with an 18 h incubation time; the pH of acceptor and donor compartments was always the same.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…14,15 Two steps are involved in the hydrolysis of CP11: initially a slow enzymatic hydrolysis of the ester bond and then a fast chemical hydrolysis of the carbamate moiety to release S-allyl-GSH, CO 2 , and HCOH (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%
“…One approach to improve the oral bioavailability of peptides and peptidomimetics is to modify their physicochemical properties by making cyclic prodrugs. Our laboratory has developed cyclic peptide prodrug methods using chemical linkers such as acyloxyalkoxy, phenylpropionic acid, and coumarinic acid (7–9). The synthetic methodology to make coumarinic acid linker was previously developed by Wang et al .…”
mentioning
confidence: 99%
“…The syntheses of cyclic prodrugs 1a–d were achieved by converging two key intermediates 5 and 8a–d to give linear precursors 9a–d . The synthesis of intermediate 5 was performed using a previously described method (23).…”
Section: Synthetic Chemistrymentioning
confidence: 99%
“…The physical characterizations of each type of intermediates (i.e. 8a, 8b, 8c, and 1-Iodomethyl-p-nitrophenyl carbonate (3), Boc-PheO ) Cs + (4), Boc-[(phenylalaninyloxyl)methyl]-p-nitrophenyl carbonate (5), and TFAAEH-Asp(OBzl)-OTce were prepared according to previous literature reports (23). Due to the side reaction, the best yield obtained for compound 5 was 37%.…”
Section: Synthetic Proceduresmentioning
confidence: 99%